Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Prima Karya Abadi Pali - Romsa Endrekson Samsi; Resi Marina (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2025)
This study aims to determine the impact of motivation and job satisfaction on the performance of employees at PT. Prima Karya Abadi Pali. The population and sample in this study consisted of 60 employees from the production division of PT. Prima Karya Abadi Pali. The research data were analyzed using multiple linear regression analysis, processed with the help of the computer program Statistical Package for the Social Sciences (SPSS) version 26.The results of this study show that both partially and simultaneously, motivation and job satisfaction have a significant influence on the performance of employees at PT. Prima Karya Abadi Pali. The F significance value of 0.000 < 0.05, with 57 degrees of freedom and an alpha of 0.05, produced the multiple linear regression equation:Y = 12.873 + 0.251X₁ + 0.448X₂ + e. Partially, the motivation variable contributes positively by 0.251 units in influencing performance, while job satisfaction contributes positively by 0.448 units in influencing the performance of employees at PT. Prima Karya Abadi Pali.